The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1118/1.4931604
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the OSC‐TV iterative reconstruction algorithm for cone‐beam optical CT

Abstract: The use of iterative reconstruction improves cone-beam optical CT image quality in many ways. The comparisons between OSC-TV and filtered backprojection presented in this paper demonstrate that OSC-TV can potentially improve the rendering of spatial features and reduce cone-beam optical CT artifacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…We can take combating strategies from three perspectives: (a) when performing scanning experiments, we should strictly follow the preparation and scanning protocol and be careful in every task, as detailed in Doran (2010); (b) in most cases, anomalies in raw data are inevitable, and we should pre-process the raw data before reconstruction, including bad pixel removal and refraction correction; (c) in reconstruction, iterative algorithms are preferred rather than commonly used filtered backprojection type algorithms (FBP for 2D geometry, and FDK for 3D cone beam geometry). Our preliminary study using the simultaneous iterative reconstruction technique (SIRT) (Yi et al 2015), revealed the potential of iterative algorithms over FBP in optical-CT noise and artefacts suppression, and following papers by other groups gave similar conclusions (Doran and Yatigammana 2012, Matenine et al 2015, Shih et al 2015.…”
Section: Introductionsupporting
confidence: 62%
“…We can take combating strategies from three perspectives: (a) when performing scanning experiments, we should strictly follow the preparation and scanning protocol and be careful in every task, as detailed in Doran (2010); (b) in most cases, anomalies in raw data are inevitable, and we should pre-process the raw data before reconstruction, including bad pixel removal and refraction correction; (c) in reconstruction, iterative algorithms are preferred rather than commonly used filtered backprojection type algorithms (FBP for 2D geometry, and FDK for 3D cone beam geometry). Our preliminary study using the simultaneous iterative reconstruction technique (SIRT) (Yi et al 2015), revealed the potential of iterative algorithms over FBP in optical-CT noise and artefacts suppression, and following papers by other groups gave similar conclusions (Doran and Yatigammana 2012, Matenine et al 2015, Shih et al 2015.…”
Section: Introductionsupporting
confidence: 62%
“…Data reconstruction of the OCT slices was performed using the ordered subsets convex algorithm with regularization via total variation (OSC‐TV) 23 from the Vista 3‐D Reconstruction software (Modus Medical, London, Canada) with 0.5 mm 3 voxel size. Subsequent data analysis, including image registration between measured and planned dose maps, was done in Python (v. 3.8, Python software foundation).…”
Section: Methodsmentioning
confidence: 99%
“…Iterative algorithms have been studied for reconstruction in the case of incomplete projection data due to refraction . Additionally, noise reduction benefits have recently been demonstrated in phantoms and in polymer gel dosimeters . However, one of the challenges associated with iterative reconstruction algorithms is that they often contain one or more empirically determined constants that control either the weighting of correction terms made at each iteration, or the aggressiveness of the denoising performed.…”
Section: Introductionmentioning
confidence: 99%
“…Matenine et al. previously applied the algorithm to cone‐beam optical CT scanning, but used projection data obtained using the DeskCAT scanner (Modus Medical Devices, Inc., London, Canada). This is a dedicated educational system, which suffers from both stray light effects and refractive index mismatch between phantoms and surrounding media.…”
Section: Introductionmentioning
confidence: 99%